2016
DOI: 10.3998/ark.5550190.p009.636
|View full text |Cite
|
Sign up to set email alerts
|

Quaternization of 2-(arylamino)aryliminophosphoranes. A route to N,N'-disubstituted 2-aminodiarylamines and unsymmetrically substituted 1-aryl-1,2,5,6-tetrahydro-1,6-benzodiazocines

Abstract: A convenient route leading to variously substituted N-alkyl-N′-aryl-o-phenylenediamine derivatives via quaternization of the imine nitrogen atom of 2-(arylamino)aryliminophosphoranes is presented. The method allows to introduce identical or different alkyl groups onto both nitrogen atoms. The N,N′-bis-allyl derivatives so obtained, after protecting the secondary amine group, easily undergo RCM cyclization providing unsymmetrically substituted 1,2,5,6-tetrahydro-1,6-benzodiazocine systems in high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In our work published in 2014 we found that the reaction of 2-nitrosodiarylamines with PPh 3 proceeded under very mild conditions and that the corresponding iminophosphoranes were formed in very good yields . Because of the presence of ortho arylamino substituent they turned out to be versatile starting materials in the synthesis of nitrogen-containing heterocyclic frameworks, guided mainly by aza-Wittig condensation. , Later we proved that the corresponding iminophosporanes can also be synthesized from 2-nitrodiarylamines, although the reaction requires elevated temperature . The finding prompted us to employ this reaction and the iminophosphoranes so formed for the synthesis of heterocyclic compounds based on 1,4-dibenzodiazepine scaffold.…”
mentioning
confidence: 99%
“…In our work published in 2014 we found that the reaction of 2-nitrosodiarylamines with PPh 3 proceeded under very mild conditions and that the corresponding iminophosphoranes were formed in very good yields . Because of the presence of ortho arylamino substituent they turned out to be versatile starting materials in the synthesis of nitrogen-containing heterocyclic frameworks, guided mainly by aza-Wittig condensation. , Later we proved that the corresponding iminophosporanes can also be synthesized from 2-nitrodiarylamines, although the reaction requires elevated temperature . The finding prompted us to employ this reaction and the iminophosphoranes so formed for the synthesis of heterocyclic compounds based on 1,4-dibenzodiazepine scaffold.…”
mentioning
confidence: 99%